Oral purpura as the first manifestation of primary systemic amyloidosis. Issue 6 (July 2016) - McCormick, Robert Stuart; Sloan, Philip; Farr, David; Carrozzo, Marco
Abstract: Oral blood blisters and purpura are rare features of primary systemic amyloidosis (amyloid light-chain (AL) amyloidosis). We report a case in which these unusual presentations led to a diagnosis of amyloidosis, which enabled effective treatment before organ failure.